ثلاثية (رسومات الكرتون، الطفل والقيم) رؤية نقدية في بعض النماذج السلبية - أسعداني, سلامي; فقيري, ليلى (جامعة الوادي - University of Eloued, 2022)
تتأثر القيم بفعل الكثير من المؤثرات الداخلية والخارجية الدخيلة على المجتمع منها تأثيرات التكنولوجيا وتفاعلاتها وكذا مضامينها مثل أفلام الكرتون الذي يعد شكل من أشكال الفنون ثنائية الأبعاد وتصوير للفن المرئي. حيث تهدف الدراسة الى معرفة القيم المتضمنة في أفلام الكرتون وتأثيرها على الجوانب المعرفية للأطفال. بالتركيز على التأثيرات السلبية لهذه الافلام من خلل استعراض لبعض النماذج. ولقد خلصت الدراسة الى نتيجة مفادها أن افلام الكرتون أَثْرت إلى حد كبير على الجوانب المعرفية لدى الطفل وأن الجوانب السلبية لأفلام الكرتون لا تقف عند حد ما. ومن الواجب على المختصين في شؤون تربية الطفل أن يفيدوا من الرسوم المتحركة في عملية التعليم، وأن يصمموا مناهج صافية متكاملة توضع إلى جانب المناهج المدرسية التقليدية . Abstract : Values are affected by many external and internal influences on society, including the effects of technology and its interactions, as well as its contents, such as cartoon films, which are a form of two-dimensional art and a depiction of visual art. Where the study aims to know the values contained in cartoon films and their effect on the cognitive aspects of children, by focusing on the negative effects of these films through a review of some models. The study concluded that cartoon films have a great influence on the cognitive aspects of the child and that the negative aspects of cartoon films do not stop at some point. It is the duty of specialists in the affairs of child rearing to make use of animation in the education process, and to design integrated extracurricular curricula to be placed alongside the traditional school curricula.
مقال
Keywords: أفلام الكرتون؛ القيم؛ تأثير؛ الأطفال؛ الدين؛ نماذج; cartoon movies;values;influence;children;religion;models